The efficiency and quality dilemma: What drives South African call centre management performance indicators? - Diane Banks; Gert Roodt (SA Journal of Human Resource Management, 2011)
Orientation: Call centres have become principal channels of communication with customers. Therefore, companies attempt to reduce costs and improve the quality of their interactions with customers simultaneously. These objectives are often conflicting and call centre managers struggle to balance the efficiency and quality priorities of the business. Research purpose: This study explored the key performance indicators that drive management practices in the South African call centre industry in the context of the dilemma between efficiency and quality.